Can the New Zealand Disability Sector Work Collaboratively Together? - Vickery, Russell (Disability Studies Quarterly, 2003)
This presentation will look at the New Zealand Disability sector and ask the question: Can groups that are fragmented and trying to gain individual respect and autonomy, work together in a manner in which they can put aside individual issues and unite in one common aim. Historical events that show how fragmented the disability sector are will be described. Recent events in the disability sector will be highlighted to show that, once a level of trust between groups can be achieved, individuals can join together. However, the challenge for the future will be to maintain that level of trust.